Lessons Learned from Reevaluating Big Deals with Unsub. Issue 3 (2nd October 2022) - Chamberlain, Scott
Abstract: The value of big deals is increasingly unclear. This article briefly discusses factors others have considered in evaluating big deals and covers the four factors that should be considered moving forward: open access, interlibrary loan, post-termination access, and a-la-carte costs. Unsub, a tool for reevaluating big deals created by the nonprofit OurResearch, is introduced. Lessons learned are shared from two years of helping libraries reevaluate big deals to provide insight into the complexities and tradeoffs involved in evaluating big deals across many libraries.